Ethnobotanical Study on the Traditional Use of Pistacia lentiscus L. Among the Local Population of Northern Central-East Region of Algeria - Aicha Blama; Zineb Fedjer; Amokrane Mahdeb; Azzedine Mazari (Turkish Journal of Agriculture: Food Science and Technology)
The botanical heritage of a region is an important resource for local people, which allows them to treat themselves with plants that have already been experienced from generation to generation for their benefits and effectiveness. The aim of this study was to highlight the different uses of lentisk pistachio products in the region of Jijel (Algeria). Systematic surveys have been carried out among different categories of people, by age group; have shown a growing interest in the use of medicinal plants. Two approaches (observation, and interview) were used to support this study, with an ethnobotanical worksheet, to obtain other recipes and more information on lentisk benefits and uses. The survey data processing showed that the lentisk is used for therapeutic purposes, to treat diseases of the skin (29%) and respiratory system (28%). The main and most used part of the plant is its berries. The plant is harvested in a spontaneous state and the picking of berries is done from November (in winter). Oil extraction is the principal preparation (72%). The use of resinous gum was not mentioned. Ten percent of surveys gave culinary recipes for some traditional meals preferred by Jijelians. The current study highlighted the ancestral practices and uses of the lentisk by Jijelians. It is necessary to develop this niche and promote its value chain in order to consolidate the economy of the local population.